Dampak Kenaikan Harga BBM terhadap RBP di Kontraktor X Karena Kelangkaan BBM di Pandemik Covid-19 - Fikran Sahid; Ryan Rachmat Fauzy (J-MAS (Jurnal Manajemen dan Sains), 2023)
The Covid-19 pandemic has had a significant impact on various sectors, including the construction industry. One of the impacts is the scarcity of fuel, which causes fuel prices to rise. In this study, we examine the impact of rising fuel prices and fuel scarcity on the Company's Cost Plan (RBP) in Contractor X. The research was conducted by interviewing the owners and managers of Contractor X and collecting data from the company's financial statements which will then be analyzed using quantitative analysis methods. The results of the study show that the increase in fuel prices and fuel shortages have an impact on increasing production costs and impacting the company's profit margins. Contractor X is faced with a new challenge to find the right solution in facing difficult market conditions due to the Covid-19 pandemic. The results of this research are that the increase in fuel prices due to the world's fuel shortages has a direct impact on increasing expenses or the cost of a project that will be carried out by construction in Indonesia. Price increases in the form of wages, materials, tools, preparation and completion as well as indirect costs have a negative impact on the construction sector in Indonesia because production and transportation costs are higher.